The impact of myocardial volume assessed with cardiac computed tomography on the prediction of coronary lesion ischemia. (25th November 2020) - Matsuda, J
Abstract: Background: Angiographical stenosis assessed by quantitative coronary angiography (QCA) is correlated with fractional flow reserve (FFR). However, there is discrepancy between severity assessed by QCA and functional ischemia assessed by FFR in non-negligible proportion. Purpose: We sought to investigate the incremental predictive value of left ventricular myocardial mass (LVM) assessed by computed tomography (CT) in addition to QCA for a significant ischemia. Methods: A total of 177 angiographically intermediate lesions which underwent FFR measurement and cardiac CT were investigated. FFR was measured with pressure-sensor wire during the hyperemia. LVM of the subtended territory to the lesion was measured with use of proprietary off-line software. Having FFR≤0.80 was considered a significant ischemia and the predictors of FFR≤0.80 was determined. Results: FFR ≤0.80 was detected in 83 (46.9%) lesions. Left anterior descending (LAD) lesion (P=0.013), Male (P=0.013), younger age (P<0.001), small diameter stenosis (DS) (P=0.003), long lesion length (LL) (P=0.003), small minimal lesion diameter (MLD) (P<0.001) and large LVM (P<0.001) were associated with FFR ≤0.80. In multivariate analysis, LAD (OR 2.36; 95% CI 1.05–5.32, P<0.001), MLD (OR 0.080; 95% CI 0.030–0.21, P<0.001) and LVM (OR 1.05; 95% CI 1.03–1.08, P<0.001) independently predicted FFR ≤0.80. Receiver-operating characteristics (ROC) analysis showed the area under the curve (AUC) was improved by combining multiple factors (DS alone, AUC = 0.63 vs DS + LAD, AUC = 0.71: P=0.029) (DS + LAD, vs DS + LAD + LVM, AUC = 0.79: P=0.0071) (Figure). Conclusion: Myocardial volume of subtended region was associated with myocardial ischemia independent of anatomical stenosis and LAD location. Funding Acknowledgement: Type of funding source: None